Endolichenic fungi extracts: A promising alternative for ultraviolet protection in cosmetics - SESAL, NÜZHET CENK (My University, 2023)
Lichen-derived extracts are a potential source for skin health products due to their antioxidant activity that can prevent damage caused by ultraviolet (UV) rays. The slow natural growth and limited reproduction of lichens limit their use. However, endolichenic fungi (ELF) from lichen thalli can serve as a more efficient, rapid, and standardized biological resource for the cosmetic industry. We aimed to investigate the UV protection of Lobaria pulmonaria, Bryoria capillaris, and Usnea sp., and isolated ELF extracts. Total antioxidant, phenolicflavonoid content, sun protection factor (SPF), and tyrosinase inhibitory activities of lichen and ELF extracts were also investigated. As a result, ELF extracts were found to have antioxidant content close to, and in some cases, much higher than lichen species. While SPF values of lichen species varied between 31.45-31.80, results close to lichens were found in the range of 6.54-32.01 values of ELF extracts. Interestingly, lichen extracts did not have tyrosinase inhibitory activity, while some ELF extracts had tyrosinase inhibitory activity in the range of 2.49-38.44. The results of this study suggest that ELF extracts may have the potential to be used as innovative UV protectants in the cosmetic industry.
Keywords: Tıp; Dahili Tıp Bilimleri; Dermatoloji; Kimya; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Dermatology; Chemistry; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Klinik Tıp; DERMATOLOJİ; Clinical Medicine (MED); Natural Sciences (SCI); CLINICAL MEDICINE; CHEMISTRY; DERMATOLOGY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences